Black Beetle Virus: Messenger for Protein B Is a Subgenomic Viral RNA - Friesen, Paul D. (1982)
Black beetle virus induces the synthesis of three new proteins, protein A (molecular weight, 104,000), protein α (molecular weight, 47,000), and protein B (molecular weight, 10,000), in infected Drosophila cells. Two of these proteins, A and α, are known to be encoded by black beetle virus RNAs 1 and 2, respectively, extracted from virions. We found that RNA extracted from infected cells directed the synthesis of all three proteins when it was added to a cell-free protein-synthesizing system. When polysomal RNA was fractionated on a sucrose density gradient, the messengers for proteins A and α cosedimented with viral RNAs 1 (22S) and 2 (15S), respectively. However, the messenger for protein B was a 9S RNA (RNA 3) not found in purified virions. Like the synthesis of viral RNAs 1 and 2, intracellular synthesis of RNA 3 was not affected by the drug actinomycin D at concentrations which blocked synthesis of host cell RNA. This indicated that RNA 3 is a virus-specific subgenomic RNA and, therefore, that protein B is a virus-encoded protein.